2020
DOI: 10.1186/s13018-020-01684-9
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol can enhance osteogenic differentiation and mitochondrial biogenesis from human periosteum-derived mesenchymal stem cells

Abstract: Background: Osteoporosis is a metabolic bone disorder that leads to low bone mass and microstructural deterioration of bone tissue and increases bone fractures. Resveratrol, a natural polyphenol compound, has pleiotropic effects including anti-oxidative, anti-aging, and anti-cancer effects. Resveratrol also has roles in increasing osteogenesis and in upregulating mitochondrial biogenesis of bone marrow-derived mesenchymal stem cells (BM-MSCs). However, it is still unclear that resveratrol can enhance osteogeni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…In this study, the ALP levels, evaluated after 7 days, were increased after the treatment with 1d at 5 µM compared to the control cells and to cells treated with RSV, while 1h did not influence the level of ALP. The results were in accordance with the study of Moon DK et al that showed enhanced ALP levels between 5 and 10 days in mesenchymal cells after the administration of 5 µM of RSV [ 40 ]. In addition, the enhanced osteoblast activity was confirmed by the analysis on mineralization features.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the ALP levels, evaluated after 7 days, were increased after the treatment with 1d at 5 µM compared to the control cells and to cells treated with RSV, while 1h did not influence the level of ALP. The results were in accordance with the study of Moon DK et al that showed enhanced ALP levels between 5 and 10 days in mesenchymal cells after the administration of 5 µM of RSV [ 40 ]. In addition, the enhanced osteoblast activity was confirmed by the analysis on mineralization features.…”
Section: Discussionsupporting
confidence: 92%
“…It performs an integral function in the healing of fractures and maintenance of bone tissues. 22 In vitro treatment with Res of primary human bone marrow stromal cells (BMSCs) in elderly patients, which were characterized by high adipocyte and low osteoblast differentiation, remarkably enhanced osteoblast differentiation and reduced adipocyte formation. 23 Res therapy reduced the degrees of NF-κB and β-catenin protein expressions in TNF-α-induced BMSCs, increased the downregulated levels of OCN and Runx2 in TNF-α-induced BMSCs, and increased the differentiation of BMSCS into osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial mass can be increased with osteogenic differentiation, resveratrol has been shown to enhance mtDNA content and mitochondrial quality in a time-dose dependent manner ( 27 ). Therefore, as a SIRT1 activator ( 28 ), resveratrol can promote mitochondrial biogenesis during osteogenic differentiation.…”
Section: The Pathological Role Of Mitochondria In Osteoporosismentioning
confidence: 99%
“…Ma ( 67 ) found that sodium hydrosulfide (NaHS) could reverse dexamethasone-induced mitochondrial dysfunction by upregulating the expression of SIRT1 and its downstream effector PGC-1α, and SIRT1 silencing abolished the protective effect of NaHS on mitochondrial dysfunction in osteoblasts. In addition, resveratrol can protect osteoblasts in osteoporosis rats by activating SIRT1 target to enhance mitochondrial biogenesis and mitophagy ( 27 , 63 ) 75 . Li ( 68 ) found that iristein decreased mitochondrial membrane potential, intracellular ROS level, mitochondrial O 2 · − state, ATP production, complex I and IV activity through SIRT3 pathway, indicating that iristein regulated mitophagy and mitochondrial biogenesis in a SIRT3 dependent manner to reverse the AGE induced inhibition of adipocyte stem cell (ASC) osteoblastic differentiation.…”
Section: Potential Therapeutic Targeting Of Mitochondria In Osteoporosismentioning
confidence: 99%